Integration of Restorative Justice in Modern Criminal Law: Legal Analysis (Al-Aasar, 2025)
This article explores the criminal justice system but with the aspect of restoration by finding the actual meaning and principles on which restorative justice will work. This system is emerged as a result of finding social harmony after delivering Justice. There are some aspects of restoration which needs to be kept in sight while performing restoration process. Further more this paper presents the historical development of restorative justice and different theories like theory of reintegrative shaming, theory of procedural justice and communitarian justice all of them focus on the main theme of restorative justice. It also provides a comparison of retribution with restoration and displays the major importance of restoration process. Not only in West but also in Islam, this process has taken place several times and it is present in Holy Quran to highlight its importance for Muslims.